2014
DOI: 10.1080/03650340.2013.871385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deficit irrigation on tomato and eggplant and their infection with the root-knot nematode under controlled environmental conditions

Abstract: Deficit irrigation has been widely investigated as a valuable strategy for dry regions where water is the limiting factor in crop cultivation. Soil moisture can be one of the important factors that influence root-knot nematode (RKN) disease development. To determine how different levels of irrigation can affect disease development, irrigation regimes ranging from 20% to full field capacity (FC) were applied to tomato and eggplant plants inoculated with Meloidogyne javanica (M. javanica) under controlled condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…Several factors can affect the results of a challenge between pathogen and host. Biological factors such as inoculant virulence, seedling development, substrate composition, inoculation conditions, greenhouse humidity, temperature and solar irradiation, may be considered (Hua, 2013;Mohawesh;Karajeh, 2014;Carvalho et al, 2015;Özalp;Devran, 2018). In addition to standardizing the conditions of the biological tests, the principles of agricultural experimentation were considered to interpret all these factors together, as effects of the environment.…”
Section: Resultsmentioning
confidence: 99%
“…Several factors can affect the results of a challenge between pathogen and host. Biological factors such as inoculant virulence, seedling development, substrate composition, inoculation conditions, greenhouse humidity, temperature and solar irradiation, may be considered (Hua, 2013;Mohawesh;Karajeh, 2014;Carvalho et al, 2015;Özalp;Devran, 2018). In addition to standardizing the conditions of the biological tests, the principles of agricultural experimentation were considered to interpret all these factors together, as effects of the environment.…”
Section: Resultsmentioning
confidence: 99%
“…The DI levels decreased M. incognita in sugarbeet accompanied by a small reduction in root and sugar yields and sugar percent at the 75% irrigation level. DI can be applied to improve the effectiveness of the present control strategies to control root-knot nematodes (Jatala, 1985;Noling andBecker, 1994 andMohawesh andKarajeh, 2014) and increase WUEs. Prot (1979) reported that the J 2s of M. javanica accumulates most highly at the highest moisture content along a soil moisture gradient.…”
Section: Data Inmentioning
confidence: 99%
“…Soil moisture is an important factor affecting nematode development and infection (Wallace, 1963;Duncan et al, 1998 andHunter 2000). Increasing water stress decreases the water potential (from 1 to 10 bars) around root-knot nematode, M. javanica, which reduces the percentage of eggs hatching and increases the percentages of second stage juveniles mortality (Mohawesh and Karajeh, 2014). For coping with water shortage and scarce supplies, deficit irrigation, defined as application of water below the full requirement of the crop, is an important tool that achieves the goal of reducing the amount of water required for irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…Drip irrigation may have the ability to reduce soil moisture-sensitive plant diseases and pests (Shin 2005 andKarajeh 2013). Also, soil moisture considered as one of the most important factor which can affect nematode population and infection (Hunter 2000: andSurega andRamakrishnan 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Also, soil moisture considered as one of the most important factor which can affect nematode population and infection (Hunter 2000: andSurega andRamakrishnan 2017). Moreover, increasing water stress can increases the second larval stage mortality and reduces the eggs hatchability of M. javanica (Mohawesh & Karajeh 2013). However, this is may be related to a particular hosts and particular localities (Norton, 1978).…”
Section: Introductionmentioning
confidence: 99%